Performance Analysis of Cluster-based Multi-UAV Routing Protocol under Various Mobility Models using NS-3 - Harry Darmawan; Prima Kristalina; Moch. Zen Samsono Hadi (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2026)
In this paper, the performance of a cluster-based multi-UAV communication system is analyzed as a means to enhance network reliability and coordination in support of Search and Rescue (SAR) operations within disaster-affected areas. The proposed approach addresses the challenges of maintaining connectivity, ensuring efficient data transmission, and facilitating effective collaboration among UAVs in critical environments. The system is designed with a four-layer architecture: Base Station (BS), Cluster Head (CH), Clustered Drone (CD), and User Equipment (UE). These layers are modeled and evaluated using Network Simulator 3 (NS-3). Three routing protocols, namely OLSR, AODV, and DSDV are evaluated under three types of UAV mobility models: Gauss-Markov, Random Waypoint (RWP), and Reference Point Group Mobility (RPGM). Quality of Service (QoS) parameters for wireless networks, such as throughput, packet delivery ratio (PDR), delay, and packet loss, are analyzed under several cluster-based UAV scenarios. The simulation results show that the cluster-based multi-UAV model using OLSR routing protocol achieves the best performance under the RPGM mobility model, with an average throughput of 67.57 kbps, 87.47% PDR, 86 ms delay, and 12.53% packet loss, outperforming the other routing protocols. The OLSR routing protocol demonstrates the highest consistency, with higher throughput and PDR values, as well as lower delay and packet loss compared to AODV and DSDV, particularly in small- to medium-scale node densities. This research contributes to the development of UAV-based cluster communication systems, particularly in terms of efficiency, stability, and adaptability to dynamic disaster environments.